Gender effect on neuromyelitis optica spectrum disorder with aquaporin4-immunoglobulin G - Kim, S-M; Waters, P; Woodhall, M; Kim, Y-J; Kim, J-A; Cheon, SY; Lee, S; Jo, SR; Kim, DG; Jung, KC; Lee, K-W; Sung, J-J; et al. (SAGE Publications, 2016)
Background Neuromyelitis optica spectrum disorder with aquaporin4-immunoglobulin G (NMOSD-AQP4) is an inflammatory demyelinating disease characterised by a high female predominance. However, the effect of gender in patients with NMOSD-AQP4 has not been fully evaluated, particularly in Asian populations. Objective To determine the effect of gender in clinical manifestations and prognosis of patients with NMOSD-AQP4 among Asians. Methods The demographics, clinical and radiological characteristics, pattern reversal visual evoked potential (VEP) test results, and prognosis of 106 patients (18 male) with NMOSD-AQP4 were assessed. Results Male patients had a higher age at onset (48.7 years vs 41 years, p =0.037), higher tendency to manifest as isolated myelitis (67% vs. 28%, p = 0.005), fewer optic neuritis attacks per year (0.08 vs. 0.27, p < 0.001), and shorter relative P100 latency on VEP testing (97.1% vs 108.3%, p = 0.001). Moreover, male gender was significantly associated with the absence of optic neuritis attacks independent of their age of onset. Conclusion In Asian NMOSD-AQP4 patients gender impacts on disease onset age and site of attack. This may be an important diagnostic clue in NMOSD-AQP4 patients with limited manifestations and suggests a better visual prognosis.